Wiki as a collaborative writing tool in the academic report writing classroom - Ibrahim, Ainol Haryati; Zailin Shah, Yusoff; Nik Mohd Alwi, Nik Aloesnita; Kassim, Asiah; Ahmad Nasaruddin, Sulaiman (2010)
Wiki is an editable Web 2.0 free authoring tool which allows users to edit or modify content, structure or design of the website directly on the page. This tool has been successfully used in businesses for collaborative planning and have now been introduced into the writing classroom. This study is aimed at investigating students' attitude toward using wiki as a collaborative writing tool in the Academic Report Writing classroom. Data from a survey and interviews are collected and analyzed. Findings from this research indicate that the most prominent factor that assists learners in the writing process is the interactivity and flexibility that this tool has to offer to the collaborative learning environment. Most learners that were involved in this study considered the ability to write, rewrite and edit on the work done in a group to be very useful, especially when this can be done fundamentally anytime and anywhere without being constrained to the class hours. The process that goes on the wiki provides means of task completion and recording of all the activities. These records are accessible to all learners and lecturer making it transparent and explicit. Nevertheless, findings also reveal that even though most students are satisfied with the use of wiki for collaborative work, it cannot surpass their preference for face-to-face (F2F) mode as well as the need for interacting with the lecturer F2F. Future researchers should thus consider approaches and strategies in facilitating more constructive interactions among learners via wiki. Another possible area that research can be conducted is on the use of wiki as part of assessment and evaluation.